Pengaruh Kebijakan Pendidikan Islam terhadap Pengembangan Karakter Religius Siswa di MAS Laboratorium IAIN SU Medan - Dea Ayunda; Dwi Rizka Nadila Lubis; Hayyun Maharani; Tengku Darmansah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study examines the influence of Islamic education policy on the development of students' religious character at MAS Laboratory IAIN SU Medan. The background of this study lies in the importance of Islamic educational institutions in shaping not only students' intellectual capacity but also their spiritual and moral identity. The study also examines how educational policies relate to curriculum, learning processes, institutional culture, and teacher roles contr To get data from teachers, students, and school administrators, a qualitative descriptive approach was used, which included observations, interviews, and documentation. The results show that students' development of religious character is significantly impacted by the adoption of Islamic education policies. Key elements that support students' faith, self-discipline, and moral principles include teacher modeling, consistent religious practices in school activities, and integrated learning between religious and general courses. Nevertheless, issues like uneven policy implementation and low teacher proficiency continue to impede the best possible results. According to the study, maintaining and enhancing kids' religious character formation in Islamic educational contexts requires professional teacher development, continuous policy execution, and close community, parent, and school involvement.